Implementation of Arabic Language Learning Evaluation in Madrasah Aliyah: a Qualitative Descriptive Study on Teachers’ Assessment Practices - Isop Syafei; Siti Ruai’ah; Naila Fauza (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to examine the implementation of Arabic language learning evaluation in Madrasah Aliyah, covering evaluation planning, the implementation of formative and summative assessments, the use of instruments assessing cognitive, affective, and psychomotor domains, the processing of assessment results, and follow-up actions such as remedial instruction, enrichment, and improvements in teaching strategies. This focus is intended to portray teachers’ actual assessment practices within the context of Arabic language learning at the Madrasah Aliyah level. The study employs a descriptive qualitative method using in-depth interviews, direct classroom evaluation observations, and document analysis, including lesson plans, assessment instruments, and student score records. Data were analyzed through the stages of reduction, data presentation, and conclusion drawing following the Miles and Huberman model. The findings indicate that teachers have implemented authentic assessments; however, the development of affective and psychomotor instruments remains insufficiently systematic. Evaluation is carried out through written tests, observations, and performance assessments of reading and speaking skills, although time constraints and large class sizes limit its effectiveness. Assessment results are processed using the e-report system, while follow-up actions include remedial programs, enrichment activities, and variations in teaching methods to enhance students’ Arabic language proficiency.